Pengambangan bahan ajar materi ekosistem berbasis pendidikan konservasi tema fauna di SDN Banjar Agung 4 - Dian Wena Anggraeni; Encep Andriana; Nana Hendracipta (Universitas Sarjanawiyata Tamansiswa, 2026)
Education is part of a lifelong learning process that takes place in all corners of life and situations that have a positive influence on the growth of each individual. Awareness and concern for the environment are very important, especially in ensuring that the environment and living creatures, including animals, can coexist. Educational institutions play an important role in instilling values that protect the environment in students. Conservation education is a way of learning to build awareness of the surrounding environment. Conservation education is a method or activity that aims to provide information and build awareness among the community, including children, teenagers, students, and community leaders. Based on interviews conducted with the school at SDN Banjar Agung 4, the teaching materials provided are those facilitated by the government, such as printed materials in the form of books. The activities provided are limited to the introduction in the books. Based on the background description, the problems in this study are how to develop teaching materials on ecosystems based on conservation education with the topic of fauna at SDN Banjar Agung 4, how feasible the teaching materials on ecosystems based on conservation education with the topic of fauna developed by teachers at SDN Banjar Agung 4 are, and how students respond to teaching materials on ecosystems based on conservation education with the topic of fauna. The objectives of this study are to identify and describe the process of developing teaching materials for conservation education with a focus on fauna, to determine the feasibility of teaching materials for ecosystem-based conservation education, and to identify student responses to teaching materials for conservation education that focus on fauna at SDN Banjar Agung 4. The research method used is a research and development method that develops products in the form of teaching materials. The results of this study show that the subject matter experts categorized the teaching materials as “Highly Feasible” for practical use in the field. Meanwhile, the media experts categorized the teaching materials as “Feasible.” These results indicate that the teaching materials are “Feasible.”